An Arctic Republic of Letters in Early Twentieth-Century Canada - Sawchuck, Christina (Nordlit, 2008)
The writing of historical polar exploration in the English-speaking academy has undergone a substantial shift in the past twenty years, to the point where it may be safe to declare that the once-dominant triumphal and hagiographical style, inherited from the nineteenth century, has breathed its last. The explorer as depicted in this tradition has become a figure of fun in current discourse, easily recognizable in the contours of caricature. Sherrill Grace, for example, presents for our inspection "courageous men battling a dangerous, hostile, female terra incognita to prove their masculinity and the superior force of their technology" whose fate is to "die nobly in struggle, or to map, claim, name, and control unstructured space, even if only on paper." It is all too simple to dismiss these aims in an era with less palpable sympathy for them. Instead, many current writers have chosen the more difficult approach of grounding these explorers in appropriate political, social, and cultural contexts, and subsequently uncovering the rationale behind their beliefs and practices.